GREEN WARRIOR: Empowering Women’s Economic Innovation Program Based on Green Sociopreneur through Mission-Based Learning Method for Economically Vulnerable Women (PRSE) in West Java - Kirani, A. A. Ayu Mirah; Kartika, Tuti; Rustanto, Bambang (SERUNAI, 2022)
Economically Vulnerable Women (PRSE) are one of the vulnerable groups affected by poverty. Thus, the strategy to accelerate poverty alleviation is not merely a matter of capital and technical skills, but also about how to instill the feeling of being able to overcome life's challenges with dignity and empowerment. The purpose of this program was to enhance innovation and productivity of Economically Vulnerable Women to become Sociopreneurs capable of establishing businesses based on the concept of Green Economy. The research location is in Cibunut Village, Sumur Sub District, Bandung City. The method involved qualitatively describing the condition of Economically Vulnerable Women and outlining the concept of Green Warrior innovation. Data collection was carried out through interviews, observations, and literature studies. Green Warrior was an innovative program designed in the form of solving a mission or challenge that involved knowledge, values, and social entrepreneurial skills. Its implementation consisted of five missions: Warrior Motivation Class, Warrior Coaching Class, Warrior Creative Class, Warrior Selling Class, and The Masterpiece of Warrior to strengthen the entrepreneurial spirit of Economically Vulnerable Women using the Mission-Based Learning method. Thus, with the presence of the Green Warrior innovation, it was hoped to drive poverty alleviation through sustainable economic growth and inclusive human development by developing human resource capacity in line with economic transformation, through skills enhancement and mentoring for vulnerable workers to become more productive, creative, and innovative, as well as being able to network as part of the supply chain to support the vision of 2045 Golden Indonesia.